The Footprint of Chinese Private Security Companies in Africa - Alessandro Arduino (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
The African continent's threat spectrum is unique in that it encompasses all the risks, from criminal to political violence, that public and private Chinese companies are likely to face as the Belt & Road Initiative continues to expand. Read Dr. Alessandro Arduino's latest policy brief as he offers a novel, high-level analysis of the security frontier in Africa and the role Chinese private security companies (PSCs) are currently playing, and will continue to play, in the African security sector.
Keywords: 330